DAMPAK BENSIN TANPA TIMBAL (Pb) PADA SEMESTER PERTAMA TERHADAP KUALITAS UDARA KOTA DENPASAR - ANAK AGUNG GEDE SUGIARTA (Environmental Research Center (PPLH) of Udayana University)
This study was to effect premium the air quality composition at Denpasar City. Theobjective test were carried out at a 3 place overload to transportation at Denpasar city andcritical quality parameters of Pb. The results indicated that the recommended air qualitycomposition is 88,298 NO2 at Gajah Mada Street and 521,48 CO at Suci Street.